Do Foreign Firms in China Incur a Liability of Foreignness? The Local Chinese Firms’ Perspective - Jiang, Fuming; Liu, L.; Stening, B. (Wiley Periodicals Inc, 2014)
Liability of foreignness has been one of the building blocks of multinational enterprise theory development, but we have limited knowledge about the liability of foreignness in the context of multinationals operating in developing countries. This study suggests that in a developing country like China, foreignness may still exist, but its negative impact on foreign firms’ performance may have become insignificant. Local Chinese firms were found to enjoy significant location-based advantages over their foreign counterparts, contributing to liability of foreignness. However, the adverse effects of liability of foreignness on foreign firms appear to be off-set by the foreign firms’ superior firm-specific and multinationality advantages over local Chinese firms. Further, the location-based advantages that foreign firms have built up over time further serve to strength their overall competitive position in China.